Climatic factors in the development and production of cocoa in Ursulo Galvan, Veracruz, Mexico - Garay-Peralta, Ignacio (2024)
Introduction. Cocoa cultivation in tropical areas is a commercially viable agroecological alternative that allows for productive diversification and sustainable soil management through the use of organic fertilization. Objective. To evaluate the development of four cocoa varieties (INIFAP 4, INIFAP 8, INIFAP 9, and Almendra Blanca) under the climatic conditions of the Úrsulo Galván region, Veracruz, Mexico. Materials and methods. An experiment was conducted between winter (December 2021) and summer (June 2022), using a completely randomized design with four treatments and ten replications. Conventional agronomic management was employed, with the addition of 10 kg of compost per tree, followed by 3 kg of vermicompost. At four months into the study, 50 g of urea, 50 g of ammonium diphosphate, and 50 g of potassium chloride were incorporated. The study included analysis of variance and Tukey’s tests (α 0.05). Results. Statistical equality was found for height, diameter, and number of branches. The cocoa’s response to temperature, precipitation, relative humidity, and wind showed that these factors influenced the expression of its productive potential, as well as its morphology and yield, without adapting to the climatic conditions under study. Conclusion. The development of the studied varieties was homogeneous based on the climatic conditions of the Ursulo Galvan region, with the Almendra Blanca variety standing out.